OSKAR UAYLDNING SHE'RIY ASARLARIDA IKKI TILLILIK DINAMIKASI: LINGVISTIK VA MADANIY O'RGANISH. (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ANNOTATION This paper explores the dynamics of bilingualism in Oscar Wilde's poetic works, emphasizing the linguistic and cultural aspects that influenced his literary style. By examining Wilde’s use of language across different cultural contexts, the study highlights how bilingualism not only enriched his vocabulary but also deepened the thematic complexity of his poetry. The analysis discusses how Wilde's exposure to multiple languages shaped his poetic expression, enabling him to navigate and intertwine various cultural nuances in his works.